The The Influence of Academic Supervision, Work Motivation, and Pedagogical Competence on the Quality of Learning Implementation - Apriliyanti, Tanti; Ysh, A.Y Soegeng; Bunyamin (IQRO: Journal of Islamic Education, 2024)
This study analyzes the influence of academic supervision, work motivation, and pedagogical competence on the quality of learning at public elementary schools in Temanggung Subdistrict, Temanggung Regency. Using a quantitative approach and correlational design, data were collected through questionnaires from 173 elementary school teachers and analyzed using multiple linear regression. The results show that all three variables have a significant impact on the quality of learning, with academic supervision contributing 29.2%, work motivation 25.4%, and pedagogical competence 41.1%. Simultaneously, these three variables contribute 49.6%. The multiple regression test indicates a significant improvement with an F-value of 57.459 and a significance level of 0.000. It is recommended that school principals enhance academic supervision and teacher competency development. Keywords: Academic supervision, work motivation, pedagogical competence, quality of learning implementation